2016
DOI: 10.1631/jzus.b1500072
|View full text |Cite
|
Sign up to set email alerts
|

Association between SMN2 methylation and disease severity in Chinese children with spinal muscular atrophy

Abstract: Abstract:The homozygous loss of the survival motor neuron 1 (SMN1) gene is the primary cause of spinal muscular atrophy (SMA), a neuromuscular degenerative disease. A genetically similar gene, SMN2, which is not functionally equivalent in all SMA patients, modifies the clinical SMA phenotypes. We analyzed the methylation levels of 4 CpG islands (CGIs) in SMN2 in 35 Chinese children with SMA by MassARRAY. We found that three CpG units located in CGI 1 (nucleotides (nt) −871, −735) and CGI 4 (nt +999) are signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 15 publications
0
15
0
Order By: Relevance
“…Studies on the methylation level of different CpGs on the SMN2 genes revealed that hypomethylation was associated with reduced disease severity [ 92 ]. In fact, SMA type 3 exhibited a lower degree of methylation in the SMN2 gene compared to type 1 or 2 patients [ 93 ]. After profiling the methylation in SMA patients and healthy controls, Zheleznyakova et al identified differential degrees of methylation at CpG sites in the following genes; CHM Like Rab Escort Protein ( CHML ), Rho GTPase Activating Protein 22 ( ARHGAP22 ), Cytokinesis And Spindle Organization B ( CYTSB ), Cyclin Dependent Kinase 2 Associated Protein 1 ( CDK2AP1 ), and Solute Carrier Family 23 Member 2 ( SLC23A2 ) [ 94 ].…”
Section: Genetic and Epigenetic Etiology Of Clinical Heterogeneitymentioning
confidence: 99%
“…Studies on the methylation level of different CpGs on the SMN2 genes revealed that hypomethylation was associated with reduced disease severity [ 92 ]. In fact, SMA type 3 exhibited a lower degree of methylation in the SMN2 gene compared to type 1 or 2 patients [ 93 ]. After profiling the methylation in SMA patients and healthy controls, Zheleznyakova et al identified differential degrees of methylation at CpG sites in the following genes; CHM Like Rab Escort Protein ( CHML ), Rho GTPase Activating Protein 22 ( ARHGAP22 ), Cytokinesis And Spindle Organization B ( CYTSB ), Cyclin Dependent Kinase 2 Associated Protein 1 ( CDK2AP1 ), and Solute Carrier Family 23 Member 2 ( SLC23A2 ) [ 94 ].…”
Section: Genetic and Epigenetic Etiology Of Clinical Heterogeneitymentioning
confidence: 99%
“…Studies suggest that epigenetic effects such as SMN2 methylation may regulate SMA disease phenotype by modulating its transcription (5961). Genome wide methylation studies have determined differences in methylation patterns in certain genes, suggesting involvement of their proteins in pathogenesis of SMA (62).…”
Section: Splicing Regulators As Modifiers Of Phenotypementioning
confidence: 99%
“…Genome wide methylation studies have determined differences in methylation patterns in certain genes, suggesting involvement of their proteins in pathogenesis of SMA (62). Discordant sibling pairs with identical SMN genotypes, suggest that epigenetic modification may control individual variations in the SMN2 function (59).…”
Section: Splicing Regulators As Modifiers Of Phenotypementioning
confidence: 99%
“…Spinal muscular atrophy (SMA) is a neuromuscular degenerative disorder in which motor neurons in the anterior horn of the spinal cord deteriorate and presents clinically as progressive muscle weakness with diminished or absent reflexes [72, 73]. Relatively common, SMA has an incidence rate of 1 in 11,000 live births [74].…”
Section: Scarna In Human Diseasementioning
confidence: 99%
“…Relatively common, SMA has an incidence rate of 1 in 11,000 live births [74]. This condition is due to the loss of the survival motor neuron 1 ( SMN1 ) gene, however, severity is determined by the gene, SMN2 [72]. Differing degrees of severity categorize the disorder into four types (I–IV), with SMA type I being the most severe and earliest onset and SMA type IV being the least severe and latest onset [72].…”
Section: Scarna In Human Diseasementioning
confidence: 99%